PELAKSANAAN KEWENANGAN BADAN KEHORMATAN DEWAN PERWAKILAN RAKYAT KOTA PEKANBARU TAHUN 2009-2014 - Annisa, Ditha Septu; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Legislature peanbaru city in demand ti perform their duties and discipline well as people representative in the pekanbaru city parliament demanded to have good ethies in carrying out his duties as a representative of the aspiration of the people, but in its implementation of the parliament internal oversight agencies to enforce the code of conduct. This research focuses on how the authority of parliament BK in resolving violations period 2009-2014 and what factors are faced BK in executing its asthority.This research is descriptive analysis is to describe the data in the studied sistematicaly using normative juridical approach that this study is based on the legislations as a positive legal norms that were estabiliherd with the BK can be elaborated and condusions drawn from the data collcted. In condusion ogf this study that the respected authority DPRD pekanbaru city in 2009-2014 should not in accordance with the result of severa things which are internal one is its wear political factor and its order code of conduct of parlement.Keyword : the exercise of authority, codes of ethics